Synthetic Mucin‐Like Glycopeptides as Versatile Tools to Measure Effects of Glycan Structure/Density/Position on the Interaction with Adhesion/Growth‐Regulatory Galectins in Arrays - Artigas, Gerard; Hinou, Hiroshi; Garcia‐Martin, Fayna; Gabius, Hans‐Joachim; Nishimura, Shin‐Ichiro (Chemistry, an Asian journal, 2017)
Functional pairing of cellular glycoconjugates with tissue lectins is a highly selective process, whose determinative factors have not yet been fully delineated. Glycan structure and modes of presentation, that is, its position and density, can contribute to binding, as different members of a lectin family can regulate degrees of responsiveness to these factors. Using a peptide repeat sequence motif of the glycoprotein mucin‐1, the principle of introducing synthetic (glyco)peptides with distinct variations in these three parameters to an array‐based screening of tissue lectins is illustrated. Interaction profiles of seven adhesion/growth‐regulatory galectins cover the range from intense signals with core 2 pentasaccharides and core 1 binding for galectins‐3 and ‐5 to a lack of binding for galectin‐1 and also the galectin‐related protein, which was included as a negative control. Remarkably, the two tandem‐repeat‐type galectins‐4 and ‐8 were distinguished by core 1 sialylation, as the two separated domains were. These results encourage further synthetic elaboration of the glycopeptide library and testing of the network of natural galectins and rationally engineered variants of the lectins. 3×G! Glycopeptides, Glycans and Galectins: Functional pairing of surface glycans with tissue lectins can be modulated by presentation and lectin structure. A microarray with tumor‐associated glycopeptides of mucin 1 and a selection of galectins show that the binding profiles of related proteins is markedly different, a perspective for a detailed structure–function analysis.